2022
DOI: 10.1016/bs.aesp.2021.11.002
|View full text |Cite
|
Sign up to set email alerts
|

How disgust affects social judgments

Abstract: The emotion of disgust has been claimed to affect a diverse array of social judgments, including moral condemnation, inter-group prejudice, political ideology, and much more. We attempt to make sense of this large and varied literature by reviewing the theory and research on how and why disgust influences these judgments. We first describe two very different perspectives adopted by researchers on why disgust should affect social judgment. The first is the pathogenavoidance account, which sees the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 148 publications
0
7
0
Order By: Relevance
“…On one hand, it is used to refer to an emotional state characterized by nausea and oral inhibition, which is usually thought to be elicited by pathogen vectors, such as bodily fluids, rotting foods, corpses, and so on. This emotion is generally thought to be part of the “behavioral immune system” in that it motivates rejection of pathogenic, contaminating substances, thus preventing illness (see Curtis et al, 2004; Faulkner et al, 2004; Inbar & Pizarro, in press; Oaten et al, 2009; Schaller & Park, 2011; van Leeuwen & Petersen, 2018). Researchers sometimes call this emotion “core disgust” (Reicher et al, 2016; Rozin et al, 2016), “pathogen disgust” (Tybur et al, 2009), or “physical disgust” (Inbar & Pizarro, in press; Lee & Ellsworth, 2013).…”
Section: Disgust: Physical Moral and Metaphoricalmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, it is used to refer to an emotional state characterized by nausea and oral inhibition, which is usually thought to be elicited by pathogen vectors, such as bodily fluids, rotting foods, corpses, and so on. This emotion is generally thought to be part of the “behavioral immune system” in that it motivates rejection of pathogenic, contaminating substances, thus preventing illness (see Curtis et al, 2004; Faulkner et al, 2004; Inbar & Pizarro, in press; Oaten et al, 2009; Schaller & Park, 2011; van Leeuwen & Petersen, 2018). Researchers sometimes call this emotion “core disgust” (Reicher et al, 2016; Rozin et al, 2016), “pathogen disgust” (Tybur et al, 2009), or “physical disgust” (Inbar & Pizarro, in press; Lee & Ellsworth, 2013).…”
Section: Disgust: Physical Moral and Metaphoricalmentioning
confidence: 99%
“…This relative dearth of evidence is largely attributable to the fact that much of the research on disgust as a sociomoral emotion has relied upon one of two approaches: correlational studies that demonstrate an association between trait disgust sensitivity and negative evaluations of outgroup members (e.g., Aarøe et al, 2017; Crawford et al, 2014; Hodson & Costello, 2007; Terrizzi et al, 2010), and experimental studies that show an effect of manipulating disgust on social or moral evaluations (e.g., Adams et al, 2014; Buckels & Trapnell, 2013; Eskine et al, 2011; Inbar et al, 2009, 2012; Rottman & Kelemen, 2012; Schnall et al, 2008; Wheatley & Haidt, 2005; Wisneski & Skitka, 2017). The correlational approach is indirect and may detect spurious associations, given the likely relevance of confounding factors, such as openness to experience (Druschel & Sherman, 1999), conservatism (Inbar & Pizarro, 2016), or emotionality more generally (Landy & Piazza, 2019).…”
Section: Prior Researchmentioning
confidence: 99%
“…For instance, the binding values in the quest to promote social order motivate group members to moralize self-control (Mooijman et al, 2018) and engage in more conspicuous status signaling (Goenka & Thomas, 2020). Relatedly, the binding values motivate increased punishment for people who engage in behaviors that would harm social order, like “deviant” sexual behaviors and insubordination (Graham & Haidt, 2010; Inbar & Pizarro, 2014; Koleva et al, 2012). Following this stream of work, we propose that binding moral values also suppress sensory consumption.…”
Section: Moral Motives and Sensory Consumptionmentioning
confidence: 99%
“…Literature found disgust toward minority groups such as nonheteronormative people (Inbar and Pizarro 2022) and observed that anti‐nonheteronormative movements commonly use themes of disgust to amplify anti‐nonheteronormative sentiments (Nussbaum 2010). Dasgupta et al.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Specifically, disgust influences the rejection of out-groups such as foreigners and socially unacceptable persons such as members of the nonheteronormative community. Disgust is closely associated with negative moral emotion toward violations of the purity of body or soul (Schnall et al 2008;Horberg et al 2009) Literature found disgust toward minority groups such as nonheteronormative people (Inbar and Pizarro 2022) and observed that anti-nonheteronormative movements commonly use themes of disgust to amplify anti-nonheteronormative sentiments (Nussbaum 2010). Dasgupta et al (2009) asserted that participants who viewed disgusting images evaluated nonheteronormative people more negatively than they did for straight people on the Implicit Association Test.…”
Section: Mediating Role Of Disgustmentioning
confidence: 99%